Frequency of myopia in childhood in Elazig (Annals of Medical Research, 2021)
Aim: We aimed to evaluate the increase in the frequency of myopia in childhood.Material and Methods: Between January 2014 and December 2018, the records of under 18 years old children with myopia diagnosed at our hospital were evaluated retrospectively. Distribution of patients of myopia was done according to years, age and sex.Results: 19,023 patients were included in the study. Mean age was 13.31±2.95. 11,261 (59.1%) of patients were female, and 7762 (40.9%) of patients were male. When the patients are categorized based on their age groups; the number of patients between 0-5 years was 181 (0.95%), the number of patients between 6-10 years was 3594 (18.8%), the number of patients between 11-15 years was 9808 (51.5%) and the number of patients aged 16 years and over was 5,440 (28.5%). When the number of patients according to years in which they applied to the hospital is analyzed; the number of patients in 2014 was 1899 (%9.9), the number of patients in 2015 was 2,768 (14.5%), the number of patients in 2016 was 3,225 (16.9%), the number of patients in 2017 was 4,781(25.1%), and the number of patients in 2018 was 6350 (33.3%). The increase in the number of patients between 2014-2015, 2015-2016, 2016-2017, 2017-2018 is statistically significant (p0.05, p0.05, p0.05, p0.05 respectively). Conclusion: The number of children with myopia is increasing day by day. Considering the budget that spent for the treatment of myopia and complications caused by high myopia, myopia must be considered as a public health problem, and necessary preventions should be taken for improving the environmental factors that are considered to be involved in etiology.
Keywords: Childhood; myopia; environmental factors